Selective drug-free cancer apoptosis by three-dimensional self-targeting magnetic nickel oxide nanomatrix. (11th October 2018) - Vijayakumar, Sivaprasad C; Venkatakrishnan, Krishnan; Tan, Bo
Aim: To develop a drug-free strategy addressing limitations of current cancer therapy.Materials & methods: A 3D self-assembled magnetic nickel oxide (NiO) nanomatrix is synthesized using femtosecond pulsed laser to mimic extracellular matrix.Results: The tunable laser pulse-interaction time and repetition rate aided in generating programmable NiO nanomatrix chemistry. The nanomatrix mimicked extracellular matrix in physical configuration and properties presenting favorable cues to cancerous HeLa cell and fibroblast cell adhesion and proliferation without cytotoxicity. The 3D nanomatrix structure altered HeLa cell behavior and induced apoptosis cancer apoptosis with an evidence of increased endocytosis when compared with fibroblast cells.Conclusion: The results demonstrate the availability of new potential avenues for magnetic drug-free cancer therapeutics.